Photocatalytic degradation of Reactive Blue 21 dye using ZnO nanoparticles: experiment, modelling, and sensitivity analysis. Issue 23 (15th October 2021) - Rodrigues, Jorge; Hatami, Tahmasb; Rosa, Jorge Marcos; Tambourgi, Elias Basile
ABSTRACT: This paper presents the photocatalysis, adsorption, and photolysis of C.I. Reactive Blue 21 dye using synthesized zinc oxide nanoparticles. The density, mean particle diameter, surface area, and porosity of the catalyst were 5550 kg/m 3, 1.19 × 10 −7, 16, 830 m 2 /kg, and 0.08, respectively. The impact of catalyst mass per volume of solution (0.2–1.0 kg/m 3 ) was experimentally investigated in terms of the percentage of dye degradation. Due to the small catalyst porosity, adsorption contributed little to overall degradation. However, the photolysis of the dye was around 12.5%, which occurred predominantly between 0 and 5 min. In the second part of the present study, the photocatalytic degradation of C.I. Reactive Blue 21 was modelled mathematically based on the mass conservation law in the solution and catalyst. The model had two adjustable variables: the convection mass transfer coefficient and the photocatalytic reaction rate constant. The model was solved numerically using the finite difference method and was validated with the experimental data. The validated model was employed to examine the impact of catalyst size and initial pollutant concentration on the photocatalytic degradation. GRAPHICAL ABSTRACT: UF0001